PENERAPAN PIDANA DENDA DALAM TINDAK PIDANA KEIMIGRASIAN PASAL 71 JO. PASAL 116 UNDANG-UNDANG NO. 6 TAHUN 2011 TENTANG KEIMIGRASIAN (PUTUSAN NO.11/Pid.C/2016/PN.JKT.BRT) - Abdullah, La Ode Dedi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
Immigration is a crime that violates the law and is protected by the law with immigration activities. The application of criminal fines for immigration offenses by not carrying out their obligations as foreigners residing in the Territory of the Republic of Indonesia, as requested by Article 71 of Law No. 6 of 2011 concerning Immigration, which reads